2022
DOI: 10.1021/acs.nanolett.2c03429
|View full text |Cite
|
Sign up to set email alerts
|

All-Electrical Spin-to-Charge Conversion in Sputtered BixSe1-x

Abstract: One of the major obstacles to realizing spintronic devices such as MESO logic devices is the small signal magnitude used for magnetization readout, making it important to find materials with high spin-to-charge conversion efficiency. Although intermixing at the junction of two materials is a widely occurring phenomenon, its influence on material characterization and the estimation of spin-to-charge conversion efficiencies are easily neglected or underestimated. Here, we demonstrate all-electrical spinto-charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The obtained transverse resistance is slightly larger than the one found in a comparable geometry of spin‐orbit readout device [ 16 ] using Bi x Se 1‐ x . A study using heavy metal‐based heterostructures reported a one order of magnitude larger transverse resistance.…”
Section: Spin‐orbit Readout Device Fabricationmentioning
confidence: 59%
See 4 more Smart Citations
“…The obtained transverse resistance is slightly larger than the one found in a comparable geometry of spin‐orbit readout device [ 16 ] using Bi x Se 1‐ x . A study using heavy metal‐based heterostructures reported a one order of magnitude larger transverse resistance.…”
Section: Spin‐orbit Readout Device Fabricationmentioning
confidence: 59%
“…[ 55 ] It is possible to separate these different contributions using a combination of systematic geometric dependencies and finite element simulations. [ 16 ] Here, these spurious effects can be ruled out using the temperature dependence of Δ R xy (Figure 2e). As shown in Figure 1d, the Hall effect is almost temperature independent.…”
Section: Spin‐orbit Readout Device Fabricationmentioning
confidence: 99%
See 3 more Smart Citations